(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research focused on the safety of the students, especially women in terms of public safety and self-awareness in school. The method of this study was qualitative in nature, and descriptive research was used. This study involved 50 selected grade 12 Accountancy, Business, and Management Strandstudents. Three variables, such as public safety, self-defense, the tool is simple to carry, and easy to use, were the effects of chili spray by using chili powder and alcohol for self-defense. Giving women protection and an effective weapon is one of the best impacts of using the chili spray as self-defense. Our survey also revealed that most of the female students agreed that using chili spray is adaptable and convenient in our society today. The results of the study revealed that using chili spray can be a good distraction against the attacker. Hence, the victims can get away easily. In particular, now that the surroundings are not safe for everybody, owning this kind of item is a relief for most of the female respondents because they will feel secure and independent. The study also revealed that you can also defend yourself against animal attacks, such as dogs and other harmless animals.